Effects of Mortality Salience on Physiological Arousal - Klackl, Johannes; Jonas, Eva (Frontiers in Psychology, 2019)
Making the inevitability of mortality salient makes people more defensive about their self-esteem and worldviews. Theoretical arguments and empirical evidence point to a mediating role of arousal in this defensive process, but evidence from physiological measurement studies is scarce and inconclusive. The present study seeks to draw a comprehensive picture of how physiological arousal develops over time in the mortality salience paradigm, and whether contemplating one’s mortality actually elicits more physiological arousal than reflecting on a death-unrelated aversive control topic. In a between-subjects design, participants were asked two open questions about their mortality or about dental pain. Cardiac, respiratory, and electrodermal indicators of arousal were measured both as participants provided written answers to the questions, and during a series of resting intervals surrounding the questions. A Bayes factor analysis indicated support for the hypothesis that the mortality salience paradigm increases physiological arousal, both while answering the two open-ended questions and afterwards. Regarding the mortality salience versus dental pain comparison, the null hypothesis of no difference was supported for most analysis segments and signals. The results indicate that the arousal elicited by mortality salience is not different from that elicited by dental pain salience. This speaks against the idea that worldview defense following mortality salience occurs because mortality salience produces higher physiological arousal. Of course, this finding does not rule the importance of other forms of arousal (i.e., subjective arousal) for mortality salience effects.